Comparison of 36 mg and 72 mg Ralgro® for suckling steer calves - Simms, D.D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
In a study in which 525 Simmental-cross steer calves were assigned to five implant treatments in four trials, 72 mg Ralgro® implants failed to increase performance significantly over' conventional 36 mg implants.
Keywords: Beef; Ralgro®; Steer calves; Performance